IDENTIFIKASI PENGARUH BUDAYA MUSIK ORANG AFRIKA-AMERIKA DALAM GERAKAN SOSIAL BLACK LIVES MATTER - Navis, Achmad Arsyad; Retnaningsih, Umi Oktyari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Africans dispersed worldwide due to slavery. Since then, they have faced racism and discrimination, which persist to this day. Their prowess in the arts, particularly music, has been utilized as a tool for their struggle. This research explores how African people in America employ their musical cultural heritage in advocating for their rights within the Black Lives Matter social movement. To discuss their struggle, the Music and Social Movements approach by William F. Danaher was employed, which has proven to be quite effective in achieving the goals or interests of a group. Data was obtained through document analysis from books, national and international journal articles, news sources, Twitter, Facebook, and Instagram posts related to the BLM movement. The research revealed that the utilization of artistic culture, especially music, involving artists and prominent individuals of African descent, resulted in positive results. Financial contributions, efforts, thoughts, and talents have boosted the spirit of African individuals residing in Western countries to advocate for their destinies. Their art, slogans, mottos, and spirit have elevated self-esteem and confidence, creating social, economic, educational, and political impacts. Keywords: Black Lives Matter, African American, Racism, Music and Social Movements.